On the nature, uses and functions of imagination in education: A multidisciplinary approach - Gelmi, Alessandro (Educational philosophy and theory, 2024)
This article aims to delve into the theoretical perspective on imagination in education, focusing specifically on Imaginative Education theory. The approach involves a dual objective: critically analyzing the limitations and specific potentials of Imaginative Education to stimulate contemporary discourse on imagination in education and using it as a foundation to frame current research in philosophy and psychology within an educational context. Key elements of this theoretical operation include a critical examination of philosophical taxonomies on the concept of imagination and its reinterpretation in relation to Predictive Coding and Embodied Cognition theories. The fundamental goal of this conceptual clarification goes beyond the theoretical realm. The article aspires to contribute to the growing interest in imagination, fantasy, and creativity as essential elements of curriculum design and teacher education, serving both as educational objectives and resources to create meaningful learning environments and experiences. Hence, the focus on the IE theory aims to bridge the gap between theoretical reflections on imagination and learning and their practical implications in curriculum design and teacher education or professional development.